Penerapan Konseling Individu Berbasis Islam Dalam Mengatasi Gamophobia (Studi Kasus Klien “W” Di Desa Kepala Siring Kecamatan Tanjung Sakti Pumu) - Tiara, Tiara; Komaruddin, Komaruddin; Jannati, Zhila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is entitled "Implementation of Islamic-Based Individual Counseling in Overcoming Gamophobia (Case Study of Client "W" in Kepala Siring Village, Tanjung Sakti Pumu District)". Gamophobia is a phobia experienced by someone who has an excessive fear of making a commitment to a partner and getting married. This study aims to find out the description of gamophobia experienced by client "W" in the village of Chief Siring before the implementation of Islamic-based individual counseling, to find out how the application of Islamic-based individual counseling to client "W" who experienced gamophobia and also to find out how gamophobia is depicted experienced by client "W" after the implementation of Islamic-based individual counseling. This study uses a qualitative approach with a case study research method. The research subject is the client "W". Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used are pattern matchmaking, making explanations, and strategic time series analysis. The results of this study indicate that before carrying out the counseling process it is still at a high level where there are several aspects that make clients experience excessive anxiety, cannot control their own thoughts, have feelings of irritability, do not want to have relationships with the opposite sex, are depressed when mentioned about marriage. The implementation of Islamic-based individual counseling was carried out in six meetings with three stages, namely the initial stage, the middle stage (work stage), and the final stage. The image of gamophobia after individual counseling based on Islam has decreased where client "W" no longer experiences excessive anxiety, is able to control himself, is able to receive input or advice from people around him.